Pengaruh faktor-faktor Internal Diri Wajib Pajak terhadap Kepatuhan Wajib Pajak Orang Pribadi - Laksmi, Kadek Wulandari; Ariwangsa, I G. N. Oka; Lasmi, Ni Wayan; Sianipar, Arsia Dondania (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
Taxes are people's contributions to the state which are mandatory, coercive in nature, and have no direct reward where they are utilized for the benefit of the state in obtaining the prosperity of the people. Tax is part of the main source of national income, which aims to finance government needs and finance development. Taxpayers must have knowledge of taxation and master the rules so they can improve compliance with their obligations so they do not get sanctions on tax rules. The research population is individual taxpayers at KPP Singaraja using a non-probability sampling method and an accidental sampling type. The research data is in the form of quantitative and multiple linear regression models. As a result, a taxpayer's knowledge of tax rules, level of income, and level of education all have a positive effect on how well they follow the rules.